Mali : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Mali reached the completion point under the enhanced HIPC initiative on March 6, 2003. Staff recommends that the Board determine that Mali qualifies for MDRI debt relief.